Geochemical Assessment of a Subtropical Reservoir: A Case Study in Curitiba, Southern Brazil - Moreton Godoi, Ricardo Henrique; Hirata, Patricia Y.; Bitterncourt, Andre V. L.; Godoi, Ana F. L.; Jafelicci, Miguel [UNESP]; dos Santos, Francisco J. [UNESP]; Bini, Rafael [UNESP]; Zara, Liuz F.; Cunha, Cynara L. N.; Soares, Ana P. K.; Gobbi, Eduardo F.; Potgieter-Vermaak, Sanja; et al. (Wiley-Blackwell, 2012)
Suspended particles and dissolved substances in water provide reactive surfaces, influence metabolic activity and contribute to the net sediment deposition. It therefore plays an important part in the ecology and quality of the water mass. The water quality in reservoirs is crucial and it is naturally maintained by flushing and sedimentation, which continuously remove phosphorus from the water. In some reservoirs, however, these removal processes are countered by recycling of ions which could play a key role to start and/or maintain the eutrophic state. The combination of macro-, trace- and microanalysis techniques can be useful to trace pollution sources through a chemical fingerprint, whether be during an acute environmental disaster or a long-term release of pollutants. The water quality and total metal content of reservoir sediments were assessed in a reservoir, situated in the capital of the Parana State, in the South-Eastern part of Brazil. The goal of this paper was to determine the metal presence in the sediment and metal and ionic speciation in the Green River reservoir water. Water and bed sediment samples, collected from various sites during 2008 and 2009, were investigated using XRF, ICP-OES, ICP-MS, XRD and zeta potential measurements. Based on the results, the heavy metal concentration and chemical composition of the suspended matter in the water samples, as well as the sediment's chemical composition will be discussed.
Keywords: Eutrophication; Heavy metals; Nutrients; Water quality